Réponses

2013-09-15T11:16:59+02:00
1) Si on choisit -2 au départ:
-2 + (-3.8) - 7.5 + 5.3 = -5.8 - 7.5 + 5.3
                                 = -5.8 + (-7.5) + 5.3
                                 = -13.3 + 5.3
                                 = -8
On obtiendra -8.

2) a. x + (-3.8) - 7.5 + 5.3
b. x - 3.8 - 7.5 + 5.3

3) -1.4 - 5.3 + 7.5 + 3.8 = -1.4 + (-5.3) + 7.5 + 3.8
                                     = -6.7 + 7.5 + 3.8
                                     = 0.8 + 3.8
                                     = 4.6
On vérifie :
4.6 - 3.8 - 7.5 + 5.3 = 0.8 - 7.5 + 5.3
                                = 0.8 + (-7.5) + 5.3
                                = -6.7 + 5.3
                                = -1.4
Le nombre initial était 4.6.

Voilà! Mais je ne suis pas sûre de tout :)